Role of moral norms in judicial decisions - Galántai Rita Tünde; Jog-erkölcs-kultúra : értékdilemmák és identitások a jogrendszerekben (2019) (Szeged) (2020)
The relationship between law and morality in judicial decision making raises several questions, such as whether morality can serve as a material source of the decision, when the judge basis its decision purely on moral norms, whether judges may deviate from the law established by the legislature referring to moral considerations, whether moral evaluation is always an essential element of the exploration of the meaning of law in judicial interpretation. In answering these problems, we need to take into account the differences between legal systems, the specificities of the investigated area of law, clarify whether the judge’s individual moral convictions or the effect of “social morality” or both are the subject of the investigation, and we have to raise the question whether the moral views of the person, who is the subject of the judicial proceeding should be taken into account. In this study, I focus primarily on the civil law area in the Member States of the European Union and the United States. Based on the civil codes, national constitutions, court decisions, and studies of legal scholars, I demonstrate in the area of civil law, which typically shows a great variety of unforeseeable cases, that moral norms have an indispensable and unquestionable role in making law function, achieve its social purpose, and settle disputes in a way, which is acceptable in the society. Based on the civil codes, I will show that this role of morality is embodied to varying degrees in the textual formulation of the codes, and when only the latter is taken into account, then the boundary between the individual legal families is blurred.
Keywords: Társadalomtudományok; Jogtudomány